Early educators' practices and opinions in relation to pre-schoolers' dietary intake at pre-school: case Finland. Issue 9 (20th February 2019) - Lehto, Reetta; Ray, Carola; Vepsäläinen, Henna; Korkalo, Liisa; Nissinen, Kaija; Skaffari, Essi; Määttä, Suvi; Roos, Eva; Erkkola, Maijaliisa
Abstract: Objective: We aimed to examine associations between early educators' feeding practices and opinions and children's dietary intake at pre-school, in a context where uniform meals are served and pre-schools are highly regulated. Design: Cross-sectional study. Food consumption data of the children consisted of two-day food records from pre-school kept by early educators. Early educators also reported their feeding practices and opinions on pre-school food. Serving style was observed. Setting: Municipal pre-schools in Southern and Western Finland. Participants: Pre-schoolers ( n 586) aged 3–6 years and early educators ( n 378). Results: Early educators' positive opinion of the food served at pre-school and the opinion that sufficient vegetables were available for the children were positively associated with children's vegetable consumption. Early educators' role modelling and a positive opinion of the food were negatively associated with children's energy intake. Encouragement to eat fruit and vegetables was associated with higher fibre intake. Intake of added sugar was low (4·4 % of energy). Conclusions: Some of the feeding practices and opinions of early educators were related to healthier dietary intake (higher vegetable consumption and fibre intake) among the children. However, in some respects, the results contradicted previous findings. Overall, early educators' feeding practices and opinions contribute to children's dietary intake and should be taken into account when promoting healthy food intake among pre-school children.